An intellectual-disability-associated mutation of the transcriptional regulator NACC1 impairs glutamatergic neurotransmission - Daniel, James A.; Elizarova, Sofia; Shaib, Ali H.; Chouaib, Abed A.; Magnussen, Helge M.; Wang, Jianlong; Brose, Nils; Rhee, JeongSeop; Tirard, Marilyn (Frontiers in Molecular Neuroscience, 2023)
Advances in genome sequencing technologies have favored the identification of rare de novo mutations linked to neurological disorders in humans. Recently, a de novo autosomal dominant mutation in NACC1 was identified (NM_052876.3: c.892C > T, NP_443108.1; p.Arg298Trp), associated with severe neurological symptoms including intellectual disability, microcephaly, and epilepsy. As NACC1 had never before been associated with neurological diseases, we investigated how this mutation might lead to altered brain function. We examined neurotransmission in autaptic glutamatergic mouse neurons expressing the murine homolog of the human mutant NACC1, i.e., Nacc1-R284W. We observed that expression of Nacc1-R284W impaired glutamatergic neurotransmission in a cell-autonomous manner, likely through a dominant negative mechanism. Furthermore, by screening for Nacc1 interaction targets in the brain, we identified SynGAP1, GluK2A, and several SUMO E3 ligases as novel Nacc1 interaction partners. At a biochemical level, Nacc1-R284W exhibited reduced binding to SynGAP1 and GluK2A, and also showed greatly increased SUMOylation. Ablating the SUMOylation of Nacc1-R284W partially restored its interaction with SynGAP1 but did not restore binding to GluK2A. Overall, these data indicate a role for Nacc1 in regulating glutamatergic neurotransmission, which is substantially impaired by the expression of a disease-associated Nacc1 mutant. This study provides the first functional insights into potential deficits in neuronal function in patients expressing the de novo mutant NACC1 protein.